Protecting Indigenous Peoples through Right to Natural Resources: Lesson from the Existence of Navajo Tribe in the United States - Widiatedja, I Gusti Ngurah Parikesit (Hasanuddin Law Review, 2015)
From the perspective of international law, indigenous peoples have the rights to own, use, and control their natural resources within their territories. In the United States, the Navajo Tribe has enjoyed those rights. In terms of law making process, this tribe can enact some acts to preserve a control over their natural resources. Specifically, the Air Pollution Prevention and Control Act, the Clean Water Act, and the Solid Waste Act. Concerning law implementation and enforcement, Navajo Tribe has a right to equitable benefit sharing in natural resources and fair court proceeding for breach. As a result, the existence of rights for natural resources requires the U.S federal government to ensure fair administration of natural resources in order to mitigate an economic exploitation of natural resources in indigenous land.